2012
DOI: 10.1212/wnl.0b013e31826d5fc3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guideline: Diagnostic accuracy of CSF 14-3-3 protein in sporadic Creutzfeldt-Jakob disease

Abstract: Objective: To assess the available evidence for the diagnostic accuracy of CSF testing for protein 14-3-3 in patients with suspected sporadic Creutzfeldt-Jakob disease (sCJD). Methods:The authors performed a systematic review of the available literature from 1995 to January 1, 2011, to identify articles involving patients who were suspected of having sCJD and who had CSF analysis for protein 14-3-3. Studies were rated according to the American Academy of Neurology classification of evidence scheme for diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 32 publications
3
91
0
6
Order By: Relevance
“…Measurement of 14‐3‐3s in CSF has been used clinically as a diagnostic biomarker for Creutzfeldt‐Jakob Disease (CJD), although recent studies have demonstrated that the specificity for CJD is lower than initially thought 48, 49, 50, 51. However, this body of research has demonstrated that 14‐3‐3 measurements in CSF are reliable and stable in patients, and can help with diagnosis in the right clinical context 48, 49. Further evaluation of 14‐3‐3 phosphorylation in CSF and plasma is indicated for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of 14‐3‐3s in CSF has been used clinically as a diagnostic biomarker for Creutzfeldt‐Jakob Disease (CJD), although recent studies have demonstrated that the specificity for CJD is lower than initially thought 48, 49, 50, 51. However, this body of research has demonstrated that 14‐3‐3 measurements in CSF are reliable and stable in patients, and can help with diagnosis in the right clinical context 48, 49. Further evaluation of 14‐3‐3 phosphorylation in CSF and plasma is indicated for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings in the NMR and EEG also appear in metabolic and toxic encephalopathies, viral encephalomyelitis (HIV and herpes virus) and paraneoplastic syndromes [5]. The positive identification of 14-3-3 protein in cerebrospinal fluid (sensitivity 92%, specificity 80%) is one of the most frequently used analytical methods for the diagnosis [6]. Mean survival usually ranges from six months to a year [7].…”
Section: Discussionmentioning
confidence: 89%
“…For the longest time, detection of 14-3-3 protein in the CSF was regarded as a highly specific test for diagnosing sCJD. 1 However, false positive elevations in CSF 14-3-3 have recently been reported in herpes simplex encephalitis, hypoxic encephalopathy, cerebral metastases, paraneoplastic disease, and metabolic encephalopathies. 2 A variety of other CSF diagnostic tests have been reported in small series, including the S100 protein, neuron specific enolase, thymosin b4, and tau protein.…”
Section: Discussionmentioning
confidence: 99%